2021
DOI: 10.1111/ijcp.14242
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quarantine competence, attitudes and practices among the public during the coronavirus pandemic: A Saudi descriptive study

Abstract: Background:The unavailability of data on the long-term efficacy of COVID-19 vaccines and of effective specific treatment, in addition to the emergence of new COVID-19 variants, makes nonpharmaceutical measures a mainstay for preventing the spread of infection. The policy responses of governments to the pandemic should be integrated with public behavioral changes. This study examines public attitudes, practices and perceived quarantine competency in Saudi Arabia during the COVID-19 pandemic. Methods:A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Health authorities should use suitable sources and social media platforms to disseminate information to the public effectively. Almarwani/ Jul 2021 82 Perceived quarantine competence, attitudes, and practices among the public during the coronavirus pandemic: A Saudi descriptive study 1022 participants Online questionnaire COVID-19 awareness programs should focus more on male and non-Saudi populations. Screening protocols/education programs for asthmatic patients to avoid confusing COVID-19 symptoms with asthma are recommended.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…Health authorities should use suitable sources and social media platforms to disseminate information to the public effectively. Almarwani/ Jul 2021 82 Perceived quarantine competence, attitudes, and practices among the public during the coronavirus pandemic: A Saudi descriptive study 1022 participants Online questionnaire COVID-19 awareness programs should focus more on male and non-Saudi populations. Screening protocols/education programs for asthmatic patients to avoid confusing COVID-19 symptoms with asthma are recommended.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…Of 386 healthcare providers in Saudi Arabia, where approximately 76% were nurses, a study reported high anxiety levels during this period, and fears of contracting MERS-CoV were high, specifically for professionals working in high-contact areas with suspected or positive virus cases ( 9 ). In March 2020, Saudi Arabia declared a national emergency due to the emergence of the COVID-19 pandemic ( 10 ), and subsequently, COVID-19’s psychological impact intensified among health care providers. The prevalence of depression, anxiety, and stress among Saudi Arabian healthcare professionals are still high ( 11 ).…”
Section: Introductionmentioning
confidence: 99%